GANGGUAN MENTAL ISTRI SEBAGAI ALASAN IZIN POLIGAMI (Tinjauan Hukum Islam atas Putusan Perkara di Pengadilan Agama Magelang No. 11/Pdt.G/2023/PA.Mgl) - Rochi, Shanti Maharanti; Mubarok, M. Ali (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2023)
This study discusses the considerations of the judges of the Magelang Religious Court in granting permission for polygamy. In this case, the applicant applied for permission to practice polygamy because his first wife had a mental disorder. This study aims to determine judges' Islamic legal considerations in making decisions. This type of research is library research, using an analytical descriptive approach. The panel of judges, in their decision, apart from being based on the juridical aspect, also referred to the rule of fiqh: